Physical – chemical basic extraction of palladium from solutions HCl by hydroxyoxime and mixture of hydroxyoximes - E. V. Volchkova; T. M. Buslaeva (Тонкие химические технологии)
The extraction of Pd(II) from solution HCl by hydroxyoxime 5-(1,1,3,3- tetrametylbutyl)-2- hydroxybenzylphenyloxime (ABP) and mixture of hydroxyoximes with kerosene has been studied. The technological schema of Pd extraction from solution HCl with use of ABP has been suggested. The extraction metod of Pd by mixture of 1015% 5-nonyl-2-hydroxybenzylloxim (Аcorga P-50) + 57% trioctylamin (ТОА) + 810% isooctanol, with high yield in wide diaposons of acidity has been suggested